Comparing the Efficacy of Excitatory Transcranial Stimulation Methods Measuring Motor Evoked Potentials - Vera Moliadze; Georg Fritzsche; Andrea Antal (Neural Plasticity)
The common aim of transcranial stimulation methods is the induction or alterations of cortical excitability in a controlled way. Significant effects of each individual stimulation method have been published; however, conclusive direct comparisons of many of these methods are rare. The aim of the present study was to compare the efficacy of three widely applied stimulation methods inducing excitability enhancement in the motor cortex: 1 mA anodal transcranial direct current stimulation (atDCS), intermittent theta burst stimulation (iTBS), and 1 mA transcranial random noise stimulation (tRNS) within one subject group. The effect of each stimulation condition was quantified by evaluating motor-evoked-potential amplitudes (MEPs) in a fixed time sequence after stimulation. The analyses confirmed a significant enhancement of the M1 excitability caused by all three types of active stimulations compared to sham stimulation. There was no significant difference between the types of active stimulations, although the time course of the excitatory effects slightly differed. Among the stimulation methods, tRNS resulted in the strongest and atDCS significantly longest MEP increase compared to sham. Different time courses of the applied stimulation methods suggest different underlying mechanisms of action. Better understanding may be useful for better targeting of different transcranial stimulation techniques.